2023
DOI: 10.3389/fnut.2023.1213223
|View full text |Cite
|
Sign up to set email alerts
|

Diet and lifestyle impact the development and progression of Alzheimer’s dementia

Abstract: Dementia is a growing public health concern, with an estimated prevalence of 57 million adults worldwide. Alzheimer’s disease (AD) accounts for 60–80% of the cases. Clinical trials testing potential drugs and neuroprotective agents have proven futile, and currently approved drugs only provide symptomatic benefits. Emerging epidemiological and clinical studies suggest that lifestyle changes, including diet and physical activity, offer an alternative therapeutic route for slowing and preventing cognitive decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 206 publications
(241 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that certain diets are effective in preventing dementia. For example, the Mediterranean diet, which is comprised primarily of vegetables, fruits, nuts, legumes, unrefined grains, fish, and olive oil, has been shown to lower the risk of cognitive decline and dementia thanks to its neuroprotective ingredients such as polyunsaturated fatty acids, polyphenols, and antioxidants [ 36 , 37 , 38 ]. However, it is not easy for ordinary people to adhere to the Mediterranean diet in their daily meals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that certain diets are effective in preventing dementia. For example, the Mediterranean diet, which is comprised primarily of vegetables, fruits, nuts, legumes, unrefined grains, fish, and olive oil, has been shown to lower the risk of cognitive decline and dementia thanks to its neuroprotective ingredients such as polyunsaturated fatty acids, polyphenols, and antioxidants [ 36 , 37 , 38 ]. However, it is not easy for ordinary people to adhere to the Mediterranean diet in their daily meals.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a balanced diet such as the Mediterranean diet could mitigate the risk of type II diabetes and confer neuroprotection. However, the mechanisms underlying these diet-associated neuroprotective effects remain unclear [59].…”
Section: Dietary Patterns and Their Influence On The Progression Of N...mentioning
confidence: 99%
“…In recent years, the Mediterranean diet has been attracting attention as a good dietary practice for dementia prevention 52,[58][59][60][61][62] . The Mediterranean diet is a dietary habit of Mediterranean countries such as Italy, Spain, and Greece, characterized by abundant use of fresh fruits and vegetables, more fish than dairy products and meat, olive oil, nuts, legumes, and often unrefined grains such as whole grains.…”
Section: Diet and Nutritional Management For Dementia Preventionmentioning
confidence: 99%